Mental Disorders and Emotional Competence Among Chinese Adolescents Before and During COVID-19 Pandemic: A Longitudinal Mediation Model - Shi, Wei; Yuan, Guangzhe Frank; Hall, Brian J.; Liu, Xiaoli; Su, Ya; Zhao, Li; Jia, Peng (Frontiers in Public Health, 2021)
Background: The outbreak of the COVID-19 pandemic has had a profound influence on the mental health and well-being of individuals across the globe. Emotional competence, defined as one's ability to recognize, understand, and manage their emotions, has been found linked with mental health problems (e.g., depression and anxiety) in previous studies. However, there is limited knowledge about the direction of the association between these factors among populations exposed to COVID-19. This study examined the possible mediation relationships between depression, anxiety, emotional competence, and COVID-19 exposure among Chinese adolescents. Methods: Responses from 7,958 Chinese adolescents who had previously taken part in a two-wave study before (December 23, 2019–January 13, 2020) and during COVID-19 (June 16, 2020–July 8, 2020) were analyzed (51.67% males, mean age = 11.74, SD = 2.15). Structural equation modeling with three covariates (i.e., age, gender, and ethnicity) was used to test the longitudinal mediation relationships between COVID-19 exposure and depression, anxiety via emotional competence. Results: Results indicated that the prevalence of depression (38.67 to 36.74%) and anxiety (13.02 to 12.77%) decreased from Time 1 to Time 2. The T2 emotional competence significantly mediated the relationship between T2 COVID-19 exposure and T2 anxiety (indirect effect [95% CI] = 0.011 [0.004–0.019], p < 0.05). T2 emotional competence also significantly mediated the relationship between T2 COVID-19 exposure and T2 depression (indirect effect [95% CI] = 0.013 [0.005–0.022], p < 0.05). The results indicated that T2 emotional competence had a significant and negative influence on T2 anxiety (β = −0.266, SE = 0.005, p < 0.001), and T2 depression (β = −0.326, SE = 0.029, p < 0.001). Conclusions: This longitudinal research study demonstrated the crucial role of emotional competence in influencing the severity of long-term mental health problems, and suggested that emotional competence interventions can be conducted to improve mental well-being among Chinese adolescents exposed to COVID-19.